ALCAM is an entry factor for severe community acquired Pneumonia-associated Human adenovirus species B - Yusang Xie; Hong Mei; Wei Wang; Xiao Li; Pengfei Hu; Xingui Tian; Rong Zhou; Jia Liu; Jieming Qu (Nature Communications)
Abstract Human adenovirus (HAdV) is a widely spread respiratory pathogen that can cause infections in multiple tissues and organs. Previous studies have established an association between HAdV species B (HAdV-B) infection and severe community-acquired pneumonia (SCAP). However, the connection between SCAP-associated HAdV-B infection and host factor expression profile in patients has not been systematically investigated. Here, we perform a CRISPR genetic screen on HAdV-B using two generations of cell surface protein-focused CRISPR libraries and identify a series of host factors including the known receptor DSG-2 and an unknown factor, activated leukocyte cell adhesion molecule (ALCAM). Further investigation shows that ALCAM affects HAdV-B infection by participating in viral internalization. Transcriptomics data from human blood samples suggests that ALCAM expression is higher in SCAP patients with HAdV-B infection than in those with other infections. Chimeric and authentic virus experiments show that ALCAM is a widely used host factor across B1 and B2 genetic clusters of HAdV-B. The dissociation constant between the knob domain of HAdV-B fiber and ALCAM is 837 nM in average. In summary, our results suggest that ALCAM is an entry factor for SCAP-associated HAdV-B.